1999
DOI: 10.1063/1.870123
|View full text |Cite
|
Sign up to set email alerts
|

Transport of a passive scalar at a shear-free boundary in fully developed turbulent open channel flow

Abstract: Direct numerical simulations of fully developed turbulence in an open channel geometry were performed in which a passive scalar was introduced. The simulations were intended to explore transport at free surfaces in two cases for which (1) the free surface was maintained at constant temperature and (2) the interfacial flux was fixed. These cases can be considered models for mass and evaporative heat transport where buoyancy and surface deformation effects are negligible. Significant differences were found in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
79
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 36 publications
16
79
1
Order By: Relevance
“…For open channel flow, DNS calculations (e.g. Handler et al 1999;Khakpour et al 2011) have shown the effect of hairpin vortical structures on scalar transport. In the present case, as described above, only relatively small tube-like structures were found and, due to the shear that was induced by the no-slip boundary conditions, no clear instantaneous correlation could be established with the gas transfer.…”
Section: Numerical Aspectsmentioning
confidence: 99%
“…For open channel flow, DNS calculations (e.g. Handler et al 1999;Khakpour et al 2011) have shown the effect of hairpin vortical structures on scalar transport. In the present case, as described above, only relatively small tube-like structures were found and, due to the shear that was induced by the no-slip boundary conditions, no clear instantaneous correlation could be established with the gas transfer.…”
Section: Numerical Aspectsmentioning
confidence: 99%
“…Tamburrino & Gulliver 2002;Banerjee et al 2004;McKenna & McGillis 2002, 2004bSugihara & Tsumori 2005;Turney & Banerjee 2013), while Laser Induced Fluorescence (LIF) enabled visualization of the gas concentration fields (e.g Wolff & Hanratty 1994;Münsterer et al 1995;Schladow et al 2002;Woodrow & Duke 2002;Herlina & Jirka 2004;Walker & Peirson 2008). Various research groups (such as Lu & Hetsroni (1995); Handler et al (1999); Nagaosa (1999); Yamamoto et al (2001)) conducted direct numerical simulations (DNS) of passive heat/mass transfer across the free surface of an open-channel flow. These studies show a number of important features such as the correlation between the vortices ejected from the bottom region and the near-surface concentration field.…”
Section: Introductionmentioning
confidence: 99%
“…Handler et al 7 compared the behavior of open channel flow with Neumann and Dirichlet boundary conditions on a passive scalar at the free surface. They found that variations of the surface flux in the Dirichlet case were much larger than variations of surface concentration when a Neumann condition was used.…”
Section: Introductionmentioning
confidence: 99%